Bioactive molecules from soybeans (Glycine max) with anti-type 2 diabetes activity: a systematic review - Rowaiye, Adekunle Babajide; Emenyonu, Lorretha Chinonye; Nwonu, Ezinne Janefrances; Okpalefe, Okiemute Ajiroghene; Ogugua, Joseph Akwoba; Akinseye, Victor Oluwatoyin; Ibeanu, Gordon Chukwuma (Academia Biology, 2024)
The hallmarks of type 2 diabetes (T2D) include peripheral insulin resistance and insulin insufficiency. Given the significance of T2D as a major public health concern, the goal of this review article is to highlight the role of bioactive properties of soybeans in the prevention, control, and management of the disease. This study examined how bioactive molecules from soybeans modulate key enzymes that affect T2D. A systematic search of electronic databases such as PubMed and Google Scholar was conducted to find relevant original studies or non-original peer-reviewed papers published on the subject. Keyword combinations such as “Soy OR soybeans”, “Soybeans AND anti-inflammatory”, “Soybeans AND anti-oxidative”, and “Soybeans AND antidiabetic” were used in the search. A search was also conducted on all the key enzymes and bioactive molecules mentioned in the review. A total of 194 articles published in English were selected. Both in vivo and in vitro experiments, and human clinical trials have proven a marked efficacy of these bioactive molecules in suppressing the key enzyme biomarkers that modulate T2D pathogenesis. Based on empirical research, the consumption of soybean products and ingredients is associated with a lower incidence of T2D. These findings will contribute to the present understanding of the therapeutic potential of soy-derived compounds. However, this study does not capture the individual variances to these biomolecules; hence, there is the need for more future pharmacokinetic studies to better understand potential interactions, safety, and more efficacy concerns.